Matemática financeira empreendedora: uma proposta de ensino, desenvolvendo a educação financeira e o empreendedorismo pessoal - Toledo, Renato Antonelli (2020)
This work dealt with the elaboration, structuring and application of a didactic sequence, through remote classes, which proposed the teaching of financial mathematics to high school students through contextualized exercises that sought to develop mathematical literacy, financial education, personal entrepreneurship and the opportunity to be protagonists in decision-making. The first meeting addressed the topic of personal entrepreneurship and percentage. In the second meeting, the theme of money was worked on, with its historical facts and its current form. Also in that same meeting, compound interest was worked through the insertion of the student body in financial contexts of people's daily lives, enabling learning. The third meeting addressed financial education and constant payment series through exercises taken from e-commerce ads and adapted to facilitate learning in the current context. In the fourth meeting, the domestic budget was worked on, favoring the application of the acquired knowledge, where the analysis of income and expenses was essential for the success of the proposed budget, seeking through an exercise, to mirror the reality experienced by a middle class family. In the fifth meeting, financial planning was worked through theory and its structuring, through mathematical calculations and a change in mentality. Since the second meeting, mathematical calculations were checked using an electronic and financial calculator that students downloaded, free of charge on their cell phones. In all meetings, a video conference application was used, a program that created slides, a group conversation application and a financial calculator application, both for smartphones. The results obtained attested that significant learning took place that gave students the ability to apply the concepts covered in real situations.